CHEBYSHEV NETS IN A SUBSPACE OF A GENERALIZED WEYL SPACE - Demirbuker, Hakan; Kanbay, Filiz (YILDIZ TECHNICAL UNIV, 2005)
Let GW(m) be m dimentional subspace of an n- dimensional subspace of an n- dimentional generalized Weyl space GW(n) and let delta = (v(1), v(2),..., v(m)) be a net in GW(m) In this paper the necessary and the sufficient condition that the net delta is to be a chebyshev net and a geodesic net relative to GW(m) and GW(n) is obtained.
Keywords: Generalized Weyl Space; Chebyshev Net; Geodesic Net; Engineering